Everyday ethics of suicide care: Survey of mental health care providers' perspectives and support needs. - Marjorie Montreuil; Monique Séguin; Catherine P Gros; Eric Racine (PLoS ONE, 2021)
Suicide occurs in people of all ages and backgrounds, which negatively affects families, communities, and the health care providers (HCPs) who care for them. The objective of this study was to better understand HCPs' perspectives of everyday ethical issues related to caring for suicidal patients, and their perceived needs for training and/or support to address these issues. We conducted a mixed methods survey among HCPs working in mental health in Québec, Canada. Survey questions addressed their perspectives and experiences of everyday ethical challenges they encounter in their practice with people who are suicidal, and their perceived needs for training and/or support therein. 477 HCPs completed the survey. Most participants mentioned encountering ethical issues when caring for people who are suicidal. The challenges HCPs encounter in their practice with people who are suicidal are numerous, including issues related to maintaining privacy, confidentiality, freedom and the therapeutic relationship. The lack of time, resources and professional support to address these issues was emphasized. Most HCPs reported that the training or education they have received does not allow them to address everyday ethical issues related to suicide care. In sum, there is a clear reported need for better training and support for HCPs who are offering care to people who are suicidal in relation to everyday ethical issues they encounter. Implications for practice include providing greater access to training, including access to specialists in ethics to address specific issues. This additional support could alleviate morally distressing situations for HCPs.